"My doctor says the cancer is worse, but I believe in miracles"—When religious belief in miracles diminishes the impact of news of cancer progression on change in prognostic understanding. Issue 4 (28th October 2019) - George, Login S.; Balboni, Tracy A.; Maciejewski, Paul K.; Epstein, Andrew S.; Prigerson, Holly G.
Abstract : Background: News of cancer progression is critical to setting accurate prognostic understanding, which guides patients' treatment decision making. This study examines whether religious belief in miracles modifies the effect of receiving news of cancer progression on change in prognostic understanding. Methods: In a multisite, prospective cohort study, 158 patients with advanced cancer, whom oncologists expected to die within 6 months, were assessed before and after the visit at which scan results were discussed. Before the visit, religious belief in miracles was assessed; after the visit, patients indicated what scan results they had received (cancer was worse vs cancer was stable, better, or other). Before and after the visit, prognostic understanding was assessed, and a change score was computed. Results: Approximately 78% of the participants (n = 123) reported at least some belief in miracles, with almost half (n = 73) endorsing the strongest possible belief. A significant interaction effect emerged between receiving news of cancer progression and belief in miracles in predicting change in prognostic understanding ( b = −0.18, P = .04). Receiving news of cancer progression was associated with improvement in the accuracy of prognostic understanding among patients with weak belief in miracles ( b = 0.67, P = .007); however, among patients with moderate to strong belief in miracles, news of cancer progression was unrelated to change in prognostic understanding ( b = 0.08, P = .64). Conclusions: Religious belief in miracles was highly prevalent and diminished the impact of receiving news of cancer progression on prognostic understanding. Assessing patients' beliefs in miracles may help to optimize the effectiveness of "bad news" scan result discussions. Abstract : Religious belief in miracles is highly prevalent among patients with advanced cancer and diminishes the impact of receiving news of cancer progression on prognostic understanding. Assessing patients' belief in miracles may, therefore, help to optimize the effectiveness of "bad news" scan result discussions.